2009
DOI: 10.1111/j.1472-4669.2009.00217.x
|View full text |Cite
|
Sign up to set email alerts
|

2‐Methylhopanoids are maximally produced in akinetes of Nostoc punctiforme: geobiological implications

Abstract: Abstract2-Methylhopanes, molecular fossils of 2-methylbacteriohopanepolyol (2-MeBHP) lipids, have been proposed as biomarkers for cyanobacteria, and by extension, oxygenic photosynthesis. However, the robustness of this interpretation is unclear, as 2-methylhopanoids occur in organisms besides cyanobacteria and their physiological functions are unknown. As a first step towards understanding the role of 2-MeBHP in cyanobacteria, we examined the expression and intercellular localization of hopanoids in the three… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
80
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(93 citation statements)
references
References 36 publications
11
80
2
Order By: Relevance
“…Hopanoids have been identified in the OM of diverse bacteria (29,(43)(44)(45)(46), and two recent studies have reported a covalently linked hopanoid-lipid A compound in rhizobial plantassociated bacteria (47,48). These observations suggest that hopanoid-lipid A ordering may be widespread among hopanoid-producing bacteria.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…Hopanoids have been identified in the OM of diverse bacteria (29,(43)(44)(45)(46), and two recent studies have reported a covalently linked hopanoid-lipid A compound in rhizobial plantassociated bacteria (47,48). These observations suggest that hopanoid-lipid A ordering may be widespread among hopanoid-producing bacteria.…”
Section: Discussionmentioning
confidence: 75%
“…Interestingly, hopanoids have also been observed in association with other specialized membranes, such as the thylakoid membranes in cyanobacteria and in the vesicle envelope of the root nodule symbionts Frankia spp. (44,45,49,50). The exact role of hopanoids in these diverse bacterial membranes is not fully understood.…”
Section: Discussionmentioning
confidence: 99%
“…In conclusion, four lines of evidence suggest that 2-methylhopanes cannot be used as biomarkers for oxygenic photosynthesis: i) hpnP is distributed across many modern bacteria that do not engage in oxygenic photosynthesis, ii) cyanobacteria are not obligate oxygenic photoautotrophs (51), iii) not all cyanobacteria make 2-methylhopanoids (17), and iv) in the cyanobacterium Nostoc punctiforme, 2-methylhopanoids localize to the outer membranes of akinetes, a survival structure that is not photosynthetically active (23). Resolving the biological function of 2-methylhopanoids in modern bacteria is, therefore, necessary to better interpret the meaning of 2-methylhopanes in ancient sediments.…”
Section: Discussionmentioning
confidence: 99%
“…Because the majority of bacterial diversity has not been cultured (22) and because the production of 2-methylhopanopids varies under different growth conditions (15,20,23), it is likely that our assessment of the taxonomic distribution of these molecules is incomplete. As a result, there is inadequate data to unambiguously interpret sedimentary 2-methylhopanes as biomarkers for cyanobacteria or other taxa.…”
mentioning
confidence: 99%
“…In modern sediments, functionalized BHPs are being explored as diagnostic for varying clades of bacteria (reviewed by ).In rocks and oils,the relative abundance of different hopane isomers can provide information about both environmental conditions during deposition, as well as maturity (Seifert and Moldowan, 1980;Brassell et al, 1983;Peters and Moldowan, 1991;Peters et al, 2005). For ancient rocks, hopanoids methylated at C-2 or C-3 have received particular attention because they have been proposed as diagnostic markers for cyanobacteria and aerobic methylotrophs, respectively (Zundel and Rohmer, 1985a,b;Summons and Jahnke, 1990;Summons et al, 1994Summons et al, , 1999Farrimond et al, 2004).A current research focus lies in understanding the cellular function of BHPs in bacteria, the genetic basis for their biosynthesis and modification, and their distribution and evolutionary relationships among extant organisms (Fischer et al, 2005;Blumenberg et al, 2006;Fischer and Pearson, 2007;Rashby et al, 2007;Doughty et al, 2009;Welander et al, 2009Welander et al, , 2010Welander et al, , 2012Bradley et al, 2010).…”
Section: Introductionmentioning
confidence: 99%